Methodological Tools For Forming an Enterprise’s Investment Strategy - STETSIUK, P. A. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2024)
The article examines the issue of forming an enterprise’s investment strategy. It emphasizes that the effectiveness of strategic decisions is determined by the choice of modern methodological tools that enable adaptation to changes in the external and internal environment, accumulation of resources for innovation, and minimization of investment risks. Scientific views on the concept, characteristics, and place of investment strategy in the enterprise management system are analyzed. The basic stages of strategy development are highlighted. Methodological approaches to the analysis of the external environment, market and influencing factors, clustering, intellectual and information systems are investigated. Research algorithms in the process of planning technical, marketing, and resource parameters of investment programs, approaches to assessing sources of financing, optimizing capital structure, and the effectiveness of investment decisions are revealed. The feasibility of implementing multi-criteria approaches, modeling, and digital platforms to improve the quality of management decisions is argued. The key role of investment strategy as a dynamic, adaptive tool that combines strategic vision and operational flexibility to achieve long-term efficiency and sustainable competitive advantages for the enterprise is emphasized.